1998
DOI: 10.1176/ajp.155.10.1437
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Neuropsychological Functioning of First-Episode and Chronically Ill Schizophrenic Patients

Abstract: Sex differences in cognitive function in schizophrenic patients are not robust findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 10 publications
4
43
1
1
Order By: Relevance
“…Our study and another two studies have indicated that male individuals with schizophrenia have more cognitive deficits than females [11][12][13]. However, other studies have reported the opposite or no gender differences in the cognitive deficits of schizophrenia [5,[14][15][16]. These conflicting results support that gender differences in the cognitive deficits in individuals with schizophrenia warrant further investigation.…”
Section: Introductioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Our study and another two studies have indicated that male individuals with schizophrenia have more cognitive deficits than females [11][12][13]. However, other studies have reported the opposite or no gender differences in the cognitive deficits of schizophrenia [5,[14][15][16]. These conflicting results support that gender differences in the cognitive deficits in individuals with schizophrenia warrant further investigation.…”
Section: Introductioncontrasting
confidence: 50%
“…A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 5 years, and were on stable doses of oral antipsychotic drugs for at least 12 months prior to entry into the study. Antipsychotic treatment consisted mainly of monotherapy with atypical antipsychotics (n=200), including clozapine (n=116), risperidone (n=66), quetiapine (n=8), olanzapine (n=4), aripiprazole (n=6), and typical antipsychotics (n=63), including haloperidol (n=16), chlorpromazine (n=13), perphenazine (n=13), sulpiride (n=18), and others (n=3).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some studies have reported that male patients appear to have more cognitive impairment than females (Goldstein et al, 1998;Seidman et al, 1997), while others have found that female schizophrenics exhibit greater cognitive deficits than males (Lewine et al, 1996). Moreover, some studies failed to find any sex differences in cognitive deficits of schizophrenia (Goldberg et al, 1995;Hoff et al, 1998). These conflicting results suggested that further study of the sex differences in the cognitive deficits of schizophrenia might benefit from examination in another non-Western culture such as China.…”
Section: Introductionmentioning
confidence: 99%
“…Bozikas et al 5 found that the degree of cognitive impairment is similar for male and female patients with schizophrenia. Similarly, Hoff et al 6 reported that females with schizophrenia performed better than males with schizophrenia in visual memory, but the difference did not remain after adjusting for symptom severity. Roesch-Ely et al 7 found no difference in working memory between females and males in either controls or patients with schizophrenia, whereas females with schizophrenia performed worse in attention tasks than males with schizophrenia.…”
Section: Introductionmentioning
confidence: 97%